Prinsip-Prinsip Mendidik Anak Dalam Amsal 29:15 dan 17 - Lamtiur Pasaribu (STT Injili Indonesia Medan, 2020)
Having children with disciplined, kind and polite behavior is certainly the dream of every parent and they will do what they think is good to educate and teach to achieve that. However, many parents do not understand properly how to teach and educate children well, specifically in accordance with God's Word. Usually children will be educated according to the experience they have experienced, educating with the aim of intellectual achievement, and the emphasis on discipline is not appropriate. The Word of God is very clear in helping educators, including parents, how to educate children properly. Proverbs 29 verses 15 and 17 provide a small section that provides guidance on how to educate children and the goals of children's education can be achieved, namely having children who are disciplined, good, obedient and in accordance with God's will. Hopefully this article can help every parent as a child educator.